Sistema de coleta de dados de consumo de água de unidades habitacionais em condomínios - Cavalcante, Flávia Valéria de Oliveira (2023)
The measurement of water consumption in residential condominiums has been done collectively, with a single water meter that measures the consumption of the entire condominium, generating a single water charge that is divided equally among all residents of the condominium, without taking into account the individual consumption of each residential unit and causing residents not to be aware of their real consumption, in addition to not paying directly for it. The solution to this is individual measurement, where water meters are installed in the branch of each residential unit to measure their consumption and, thus, rationalize the use of water and charge proportionally to this consumption. The objective of this work was to develop a digital and autonomous system, which was capable of individually measuring water consumption. In this system, consumption is measured by a Hall effect sensor, controlled by an STM32 microcontroller, which sends, with the help of an Arduino Nano and an NRF24L01 module, the consumption data obtained to a Raspberry Pi. There, they are stored in a database, connected to an internal network of the condominium, which can be accessed through a web page. Although the consumption measurement system still has a lot of potential for improving and perfecting its functions, it is not can deny the evolution that the project has had so far and that it has managed to fulfill exactly what was proposed.